2013
DOI: 10.1111/ijac.12087
|View full text |Cite
|
Sign up to set email alerts
|

SiSiC Heat Exchangers for Recuperative Gas Burners with Highly Structured Surface Elements

Abstract: Heat exchangers are used in gas burners as recuperators. Their efficiency is proportional to their surface which is usually limited by the burner length and diameter. Ceramic recuperators used nowadays in industrial burners are tubular. We studied and developed a new generation of ceramic heat exchanger with the final goal of increasing the efficiency or, at similar efficiencies, of reducing their size and weight. A commercial SiSiC heat exchanger component was used to guarantee safety and robustness. The use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Structured catalysts and reactors are a class of process intensification tools to enhance the transport phenomena in catalytic processes, especially the highly exothermic or endothermic catalytic reactions such as methanol‐to‐propylene (MTP) and DRM 19‐26 and CO 2 hydrogenation 27 . Structured catalysts based on open‐cell silicon carbide (SiC) foams are particularly advantageous for high‐temperature chemical conversion processes due to their unique combination of properties, such as high‐temperature strength, thermal shock resistance, high thermal conductivity and high surface‐to‐volume ratio and high mechanical strength, for improving heat transfer 28,29 . Additionally, the cellular open structure of SiC foam also provides high permeability, low pressure drop, as well as improved axial and radial mixing of reacting streams 30‐34 .…”
Section: Introductionmentioning
confidence: 99%
“…Structured catalysts and reactors are a class of process intensification tools to enhance the transport phenomena in catalytic processes, especially the highly exothermic or endothermic catalytic reactions such as methanol‐to‐propylene (MTP) and DRM 19‐26 and CO 2 hydrogenation 27 . Structured catalysts based on open‐cell silicon carbide (SiC) foams are particularly advantageous for high‐temperature chemical conversion processes due to their unique combination of properties, such as high‐temperature strength, thermal shock resistance, high thermal conductivity and high surface‐to‐volume ratio and high mechanical strength, for improving heat transfer 28,29 . Additionally, the cellular open structure of SiC foam also provides high permeability, low pressure drop, as well as improved axial and radial mixing of reacting streams 30‐34 .…”
Section: Introductionmentioning
confidence: 99%
“…SiSiC cellular ceramics are currently industrially employed as burner components [5] at high temperatures ( $1400°C) in oxidative conditions. Indeed, porous SiSiC has proven to withstand long operating conditions in a combustion environment [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, an extensive exploration by material developers within the framework of the project revealed that out of several possibilities, the wire-loop structure is the most stable and the easiest to realize during fabrication. Creation of ceramic wire-loop structures, using the described process, has been already accomplished and reported in the literature [20]. As it stands, however, a thorough literature review reveals that the heat transfer enhancement capabilities and the associated pressure drop of these structures still remain undetermined.…”
Section: Nomenclaturementioning
confidence: 99%
“…Since l e /d h ratio for the test channel was only about 30, and since the flow was completely turbulent, fullydeveloped flow condition was not expected for any Reynolds number. Therefore, although there are several other correlations available in the literature for such channels [26], the empirical correlation proposed by Gnielinski [31], which is also quite popular owing to its accuracy and is valid even for the developing section, was adopted in the present investigation for comparison: (20) where the Darcy friction factor f, appearing in Eq. (20), had to be calculated according to the accompanying correlation, also suggested by Gnielinski [31], although this correlation does not take into account the effect of developing section:…”
Section: Validation Of the Test Set-upmentioning
confidence: 99%